Creative Thinking Counseling Teaching Program can Improve the Creativity, Creative Tendency, and Self‐Concept of Grade 7 Students: A Quasi‐Experimental Study. (5th March 2021) - Huang, Shih‐Yuan; Ko, Pei‐Jung; Lin, Hsiao‐Hui; Dai, Ru‐Huei; Chen, Hsueh‐Chih
Abstract: We developed a Creative Thinking Counseling Teaching Program (CTCTP) for Grade 7 students using the self‐concept of the counseling curriculum as the primary development axis and investigated how this program influences creativity, creative tendency, and self‐concept. We adopted a non‐equivalent control group pre‐test–post‐test quasi‐experimental design. Of 133 participants, the experimental group (67 students) received an eight‐week CTCTP, involving a 45‐minute class per week; the control group (66 students) participated in general counseling. Research instruments included the NTCT‐Figural Exercises (NTCT‐Figural), The Williams Assessment of Creative Tendency (WACT), and Elementary School Student Self‐Concept Scale (SCS). Personal reflection learning sheets, learning achievement assessment, and course feedback forms were used to qualitatively analyze the learning effectiveness and feasibility of the teaching program. Results showed that the experimental group had significantly higher scores than the control group for creativity, creative tendency, and self‐concept. Further mediation analysis showed that the effects of the teaching experiment were not the result of mutual mediation effects. Students' feedback on the CTCTP learning process suggested that it had a positive effect on the development of students' creativity, creative tendency, and self‐concept, while also meeting their learning needs. We propose recommendations for application in teaching practice and future research.